2020
DOI: 10.1111/pim.12775
|View full text |Cite
|
Sign up to set email alerts
|

Association of cytokine gene polymorphisms with susceptibility to cutaneous leishmaniasis in a Turkish population

Abstract: Human leishmaniasis is a vector-borne disease caused by intracellular protozoan parasite species belonging to the genus Leishmania (over 20 species), and it is transmitted to human by the bite of infected female phlebotomine sand fly (Phlebotomus spp. in the Old World and Lutzomyia spp. in the New World). 1,2 There are three main clinical forms of Leishmaniasis: cutaneous leishmaniasis (CL), mucocutaneous leishmaniasis (MCL) and visceral leishmaniasis (VL). 3 According to the World Health Organization (WHO) fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…1 ). The studies excluded from the meta-analysis had polymorphisms which the other included studies did not cover; therefore, it was not possible to compare them 28 . The references of all eligible publications were crosschecked, and no further records were found to meet the inclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1 ). The studies excluded from the meta-analysis had polymorphisms which the other included studies did not cover; therefore, it was not possible to compare them 28 . The references of all eligible publications were crosschecked, and no further records were found to meet the inclusion criteria.…”
Section: Resultsmentioning
confidence: 99%
“…Sonon et al 24 and Covas et al 26 , both analysing the rs180071 IL-10 SNP, indicated that IL-10 is not associated with CL and that the SNP does not regulate IL-10 secretion. Kirik et al 28 analysed the rs1800896 SNP and presented a deviation from HWE both in patient and control groups, and thus could not compare the risk estimate results. Both Hajilooi et al 25 , 30 studies demonstrated SNP influence in the progression of VL, particularly, rs1800871 and 1800896 IL-10 SNPs, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, high levels of this cytokine can lead to tissue damage and the formation of persistent lesions. Despite the existence of numerous polymorphisms within the TNF gene locus, it is not yet certain whether these polymorphisms have a direct impact on TNF-α levels 41 . This suggests that the TNF gene might be linked to how susceptible people are to leishmaniasis.…”
Section: Discussionmentioning
confidence: 99%